A nail through the urethra in urinary bladder: A case report of autoerotism (Indian Journal of Case Reports, 2020)
Autoerotic stimulation, psychosexual disorders, drug intoxication, iatrogenicity, penetrating injury, or migration from neighboring organs are common causes for an intraurethral foreign body. As per our knowledge, our patient is the first case with a self-inserted intraurethral metallic nail in prostatic urethra and bladder. A nail was found in prostatic urethra and bladder which had migrated during sexual stimulation. We successfully removed the urethral foreign body with the combined approach of percutaneous suprapubic cystostomy and cystoscopy. First-line treatment must be endoscopic manipulation, but sometimes the combined approach may be necessary. A psychiatric evaluation must be done. It can be simply avoided by psychiatric counseling to prevent its recurrence.